DEVELOPMENT OF ANTI MOSQUITO LOTION MADE FROM CLOVE (SYSYGIUM AROMATICUM), LANGUSEI (FICUS MINAHASSAE), AND APIS DORSATA BINGHAMI HONEYCOMB PLANTS - Hermanus, Britney Putri; Naharia, Orbanus; Mokosuli, Yermia Semuel (Jurnal Review Pendidikan dan Pengajaran, 2024)
Mosquitoes are the main insect vectors that cause various tropical diseases, including malaria, filariasis, and various viral diseases, such as dengue fever. Indonesia is a country with a tropical climate whose environmental characteristics are very supportive of mosquito breeding. Mosquitoes are infectious vectors that must be controlled. Efforts to control mosquito vectors include using repellents. Repellent is a chemical that can keep insects away so that insect bites can be avoided. This research aims to determine the formula for anti-mosquito lotion made from cloves, langusei, and beehives and to determine the results of organoleptic, physical tests, and the strength of repellent anti-mosquito lotion made from cloves, langusei, and beehives. The method used in this type of research is the laboratory experimental method. The samples used in this research were clove leaves, langusei, and honeycomb. The analyses carried out were organoleptic tests, pH tests, homogeneity tests, and protection power tests. The lotion, with the addition of clove, langusei, and honey bee hive plant extracts, meets the organoleptic test, test requirements for physical quality and repellent lotion strength, namely having a smooth and soft lotion mass, the color and aroma of the lotion is typical of a mixture of clove, langusei, and honey bee hive plants. The results of the study showed that from variations in the concentration of cloveleaf extract, langusei, and honey bee nest (0%, 0.25%, 5%, 10%), the best results were formula IV, namely with a concentration of 10% which had the best physical properties, safe to use and the most effective protective power to repel mosquitoes.